Improving silage digestibility with fibrolytic enzymes - Eliasson, Thomas (SLU/Dept. of Animal Nutrition and Management (until 231231), 2018)
In Sweden, the dairy cow is an important producer of both milk and meat. The production is highly dependent on forage as a source of nutrients for the cow. Ruminants are excellent converters of plant material that otherwise is highly indigestible for humans. Though, the vegetation period in Sweden is short and must supply all forage needed to feed the cow throughout the year. By harvesting later than normal, more plant biomass is produced on the expense of digestibility. This thesis comprises two parts, one literature review followed by a laboratory trial. The first part evaluates what happens inside the plant during plant maturation and if there is a way to improve digestibility in a late harvested crop. The effect of maturation was different between types of plants. The fiber content increased at a more major extent for legumes than temperate grasses (C3). On the contrary, grasses reduced their digestibility at a more major extent than legumes. The observed nutritional changes during maturation mainly originated from cell wall growth within tissues of the plant stems; mostly in vascular tissue of legumes and spread over different tissues in grass. From these observations, a laboratory trial was setup to test if different fibrolytic enzymes can digest the cell walls and improve digestibility of a late harvested crop. A late second cut harvest of mixed grasses and red clover was chopped, pre-wilted (~35 % DM) and mixed (1:1). The forage mix was treated with hemi-cellulases & cellulases (Hem & Cell), pectinases (Pect) and three ferulic acid esterases (FAE 1, 2 & 3). The five treatments and a control were ensiled as triplicates in 1.7 L glass jars for 60 days. Silage pH showed significant differences for the Hem & Cell (4.68) and FAE 3 (4.82) treatments in comparison to the control (4.75). The generally higher silage pH than normal was believed to be caused by a low water-soluble carbohydrate content (3.54 % of DM) in the forage. Further silage quality analysis showed an average ammonia-N of 8.17 % of total N and an average DM loss during ensiling of 3.3 % of DM. Silage was evaluated stable for 10 days of exposure to oxygen. DM, OM and in vitro OM digestibility showed no significant differences between treatments. The fiber content (NDF) and calculated hemi-cellulose showed no significant differences between treatments. For ADF, a significantly reduced concentration (% of DM) was seen for the Hem & Cell (27.9) and Pect (27.8) treatments compared to the control (28.9). In vitro gas production kinetics was estimated with the AMPTS II system from Bioprocess Control, Lund, Sweden. Total volume per observation was 350 ml with a 1:9 rumen fluid to buffer ratio and ~4 g DM of fresh silage sample was used. Silage triplicates were considered as blocks and run as separate runs. Treatments did not affect cumulative gas production. The gas flow (% of total) at 24–36 h were significantly lower for the Hem & Cell (16.3) treatment compared to the control (19.5). The effect of block was significant for both cumulative gas production and gas flow. Finally, no significant differences were found for OM and DM disappearance estimations of residues from the in vitro gas production kinetics analysis. The conclusion from the trial was that enzyme treatments had no clear effect on digestibility in the late harvested forage.